Postremission therapy with repeated courses of high‐dose cytarabine, idarubicin, and limited autologous stem cell support achieves a very good long‐term outcome in European leukemia net favorable and intermediate‐risk acute myeloid leukemia. Issue 5 (29th September 2020) - Borlenghi, Erika; Cattaneo, Chiara; Cerqui, Elisa; Archetti, Silvana; Bertoli, Diego; Bellotti, Daniela; Gramegna, Doriana; Soverini, Giulia; Oberti, Margherita; Schieppati, Francesca; Pagani, Chiara; Passi, Angela; et al.
Abstract: Consolidation treatment in acute myeloid leukemia (AML) patients achieving complete remission (CR) is warranted. High‐dose cytarabine (HDAC) is considered first choice in favorable risk and an option in intermediate‐risk AML. However, its optimal dose and schedule, as well as the benefit of additional chemotherapy agents remain controversial. Herein, we report on the long‐term outcome of consecutive unselected AML patients treated with repeated courses of HDAC, with the addition of idarubicin, followed by autologous peripheral blood stem cell (PBSC) support, in order to limit toxicity, according to Northern Italy Leukemia Group (NILG) AML‐01/00 study (EUDRACT number 00400673). Among 338 patients consecutively diagnosed from 2001 to 2017 at our center, 148 with high‐risk AML (adverse cytogenetic, isolated FLT3‐internal tandem duplication mutation, refractory to first induction) were addressed to allogeneic stem cell transplant. All other cases, 186 patients (55%), median age 53 (range 19–75), were considered standard‐risk and received the NILG AML‐01/00 program. After achieving CR, patients were mobilized with cytarabine 8 g/sqm to collect autologous CD34+‐PBSC and received three consolidation cycles with HDAC (20 g/sqm) plus idarubicin (20 mg/sqm) per cycle, followed by reinfusion of limited doses of CD34+ PBSC (1‐2x106/kg). The program was completed by 160 (86%) patients. Toxicity was acceptable. Neutrophils recovered a median of 10 days. Treatment‐related mortality was 3/160 (1.8%). After a median follow‐up of 66.4 months, overall survival (OS) and relapse‐free survival (RFS) at 5‐years were 61.4% and 52.4%, respectively. Twenty‐eight selected patients aged >65 had similar outcomes. According to European leukemia net‐2010 classification, the OS and RFS at 5‐years were 76.4% and 65% in favorable risk, without differences between molecular subgroups, 52.3% and 47.2% in Intermediate‐I, 45.2% and 36.5% in Intermediate‐II risk patients, respectively. In conclusion, consolidation including repeated courses of high dose cytarabine and idarubicin, with limited PBSC support, proved feasible and very effective in nonhigh risk patients. The incorporation of novel agents in its backbone may be tested to further improve patient's prognosis.